Pelaksanaan Pendidikan Agama di SMA Katolik Soverdi Kabupaten Badung Bali - Mulyani Mudis Taruna (Balai Penelitian dan Pengembangan Agama Semarang, 2010)
This research was conducted at SMA Catholic Soverdi under umbrella ofCatholic foundation in Badung district Bali Province. Focuses of this study are,implementation of religious education was seen from the aspects of curriculumimplementation, influencing factors of curriculum implementation. Thisis a qualitative research. Finding of the research depicts that developmentof the religious education’s curriculum uses curriculum set by ministry ofeducation. This affects in developing of atmosphere of religious life at school.Substantially, implementation of curriculum on religious education areable to provide services for students, namely giving religious education fitwith students’ religion, and the teacher’s religion is the same as student’s religion.DI SMA KATOLIK SOVERDI KABUPATEN BADUNG BALIKeywords : Relegius education, curiculum